ANALISIS FAKTOR YANG MEMPERANGURUHI KEPUASAN PASIEN BADAN PELAYANAN JAMINAN SOSIAL (BPJS) KESEHATAN PADA RUMAH SAKIT JABODETANG - Soekiyono, Soekiyono (Derivatif : Jurnal Manajemen, 2017)
This aims of this research to determine the effect of service quality on hospitals patient satisfaction in Jakarta. The specific objective is to determine the reliability, responsiveness, assurance, empathy and tangible of the hospitals patients satisfaction. Research carried out on 125 patients admitted to hospital use BPJS. The analytical method used in this research is path analysis with SEM AMOS software.Based on the analysis of data it can be concluded reliability, responsiveness, assurance, empathy and tangible have positive influence on hospital BPJS patient satisfaction. The advice could be given to hospitals to improve patient satisfaction is to improve the quality of services consisting reliability, responsiveness, assurance, empathy and tangible. Implications for future research is to explore the service quality variables other than the variables that have been studied so that the resulting model is more fit and the determination coefficient is greater.Â Keywords: Quality of care, patient BPJS